A ressignificação de saberes docentes nas ações dos professores supervisores do PIBID de Geografia da UEPB - Campina Grande. - Morais, Nathália Rocha (2018)
This work analyzes the re-signification of the teaching knowledge from the practices of supervisors of the Geography Subproject of the Institutional Program of Initiatives for Teaching (PIBID) of the State University of Paraíba (UEPB), Campus I, in Campina Grande. In this sense, this study focuses on the investigation of the knowledge of experience produced daily by supervisors, for whom the school environment is a space for training and production of knowledge from pedagogical practice. Therefore, Continuing Education is also one of the focuses of this analysis since the teaching path symbolizes the constant commitment to the improvement of the practices as well as to the use of the different teaching knowledge, among them those of experience. Eight teachers of the Geography / PIBID / UEPB Subprojectparticipated in theresearch developed in public schools in the city of Campina Grande-PB between the years 2012 to 2018. The methodological approach adopted in the study followed the principles and procedures of collaborative research which involved the participants in the construction of all stages of this work. Initially, the eight supervisors were willing to reflect on their teaching practices at school and the supervision of PIBID grantees. These reports of practice indicated, among several contents and teaching methodologies, that Cartography was the most difficult subject to be worked in the school space. Thus, in the second stage of the research, a workshop was organized and involved with PIBID supervisors and scholars, in order to contemplate the main obstacles related to cartographic contents approach. However, during the months of September to December of 2017, for the analysis of the interviews and the planning of the workshop, there were changes in the PIBID that led to the reduction of fellowships, leaving supervisors, and culminating in the closing of the Program in February 2018. With the reduction of the number of supervisors who participated in the last activity of the research - the workshop - the sense of collaboration was maintained and the results were very positive reflecting in the understanding of the content approached by the supervisors teachers with PIBID, as well as in the perception of ways more effective and dynamic to bring such knowledge into the classroom. In addition, those involved demonstrated satisfaction when they were active participants in the elaboration of this research whose main objective is to foster the university-school relationship and the reflection of the teaching practice of Geography.